From Classical Epistemology to Digital Scholarship: A Paradigm Shift in Contemporary Scientific Construction - Susanti, Riri; Santoso, Budi; Ahida, Ridha; Nasution, Soibatul Aslamiah (Ahlussunnah: Journal of Islamic Education, 2025)
This study analyzes the epistemological shift from the classical paradigm to digital scholarship as a form of contemporary scientific construction. Using a qualitative-descriptive approach based on the analysis of the philosophy of science and critical literature review, this study traces the changes in the concepts of truth, authority, and scientific validity resulting from the digitization of knowledge practices. Classical epistemology, rooted in rationality, empiricism, and objectivity, is now shifting towards an open knowledge system that emphasizes collaboration, transparency, and interdisciplinary connectivity. The results of the analysis show that digital infrastructure, algorithms, and big data form a new regime of truth, in which scientific validity is determined through global network participation, not solely by hierarchical verification by academic institutions. Through a synthesis of the ideas of Kuhn, Foucault, Latour, Gibbons, and Borgman, this study formulates the concept of reflexive digital epistemology, which is a scientific model that is socially and technologically aware, collaborative, open, and ethical. This study emphasizes the importance of a new scientific evaluation paradigm based on openness, epistemic justice, and digital responsibility, while highlighting the risks of algorithmic bias, data coloniality, and access inequality in the evolving practice of global digital science.